SORL1 gene mutation and octapeptide repeat insertion in PRNP gene in a case presenting with rapidly progressive dementia and cerebral amyloid angiopathy. (22nd July 2022) - Cencini, Federica; Catania, Marcella; Di Fede, Giuseppe; Rossi, Giacomina; Chalouhi, Katia Khouri; Manfredi, Chiara; Giaccone, Giorgio; Tiraboschi, Pietro; Bersano, Anna; Groppo, Elisabetta; Rosci, Chiara; Tancredi, Lucia; et al.
Abstract: Background and purpose: Cerebral amyloid angiopathy (CAA) has been associated with a variety of neurodegenerative disorders, included prion diseases and Alzheimer's disease; its pathophysiology is still largely unknown. We report the case of an 80‐year‐old man with rapidly progressive dementia and neuroimaging features consistent with CAA carrying two genetic defects in the PRNP and SORL1 genes. Methods: Neurological examination, brain magnetic resonance imaging (MRI), electroencephalographic–electromyographic (EEG–EMG) polygraphy, and analysis of 14‐3‐3 and tau proteins, Aβ40, and Aβ42 in the cerebrospinal fluid (CSF) were performed. The patient underwent a detailed genetic study by next generation sequencing analysis. Results: The patient presented with progressive cognitive dysfunction, generalized myoclonus, and ataxia. Approximately 9 months after symptom onset, he was bed‐bound, almost mute, and akinetic. Brain MRI was consistent with CAA. CSF analysis showed high levels of t‐tau and p‐tau, decreased Aβ42, decreased Aβ42/Aβ40 ratio, and absence of 14.3.3 protein. EEG–EMG polygraphy demonstrated diffuse slowing, frontal theta activity, and generalized spike‐waves related to upper limb myoclonus induced by intermittent photic stimulation. Genetic tests revealed the presence of the E270K variant in the SORL1 gene and the presence of a single octapeptide repeat insertion in the coding region of the PRNP gene. Conclusions: The specific pathogenic contribution of the two DNA variations is difficult to determine without neuropathology; among the possible explanations, we discuss the possibility of their link with CAA. Vascular and degenerative pathways actually interact in a synergistic way, and genetic studies may lead to more insight into pathophysiological mechanisms. Abstract : We report the case of an 80‐year‐old man with rapidly progressive dementia and neuroimaging features consistent with cerebral amyloid angiopathy (CAA) carrying two genetic defects: a single octapeptide repeat insertion in the PRNP gene and the E270K variant in the SORL1 gene. Although the specific pathogenic contribution of the two DNA variations is difficult to determine, we discuss the possibility of their link with CAA. Vascular and degenerative pathways interact in a synergistic way, and genetic studies may lead to more insight into pathophysiological mechanisms.